Trançando histórias, tecendo trajetórias: A consciência diaspórica em Americanah, de Chimamanda Adichie - Araújo, Eliza de Souza Silva (2017)
The present work aims at analyzing the novel Americanah (2014), by Chimamanda Adichie, concentrating on the diasporic consciousness presented in the narrative through the lens of cultural and gender studies as a means to a theoretical contextualization of the impacts of contemporaneous moves on the moving subjects. We draw our attention to the characters Ifemelu and Obinze, protagonists of the disporic move, while mainly addressing Ifemelu’s move, as she is the protagonist in the novel. The character’s shaping of a diasporic consciousness emerges from the writing of a blog that she generated while living in the United States. In the blog, she raises readers’ awareness to issues of race and gender. Her writing and her discoveries continue to take place until she moves back to her home country, Nigeria. Once she is back in Africa, she creates a new blog and reflects on the feeling of estrangement she experiences in her own culture. In order to approach the diasporic consciousness, it becomes necessary to observe the emergence of several spaces in the narration and reflect upon the function of such fictional element in the cultural dimension of a diaspora. To better understand narrative space in this context, we draw upon the considerations of Borges Filho (2007), Almeida (2013), Brandão (2012), Bakhtin (2014), amongst others. We also consider of utmost importance to signify the foreign space in Americanah as a post-colonial one and to do so, we observe the theories of Neves de Souza e Barzotto (2016), Keefer (2006) and Ogwude (2011). We realize that in the novel, the postcolonial position is revealed via narrative focus, which brings out the main characters’ perspectives. With the intention of clarifying such interpretation, we bring the propositions of Leite (2002), Jahn (2007), among others. Finally, we analyze the diasporic consciousness unraveled in the return, going back to examples presented in the literary text of a new poetics of belonging. We look into the writings of Hall (2015), Porto (2012) and Almeida (2015), whose reflections reinforce that a change occurs in subjects who experience a diaspora. We also regard the blog as a means to readaptation to the home culture and, on a broader spectrum, we interpret the act of writing as a pathway in the process of self-awareness, learning and belonging to one’s own home country and culture.